LOCATING LEARNER-CENTERED INSTRUCTION IN ISLAMIC BOARDING SCHOOLS’ CLASSROOMS: PROSPECTS AND CHALLENGES - Emawati, Emawati; Zulfikar, Teuku; Habiburrahim, Habiburrahim; Sundusiyah, Anis (Universitas Islam Negeri Ar-Raniry, 2024)
Progressive Education (PE) aims to promote students' active participation and involvement in the learning process. PE strongly supports learner-centered instruction (LCI), enabling students to be active participants rather than passive recipients of knowledge. Nevertheless, the LCI has not yet gained popularity in the Indonesian school settings, particularly in Modern Islamic Boarding Schools. This enables us to do research on the potential and obstacles of implementing the LCI as required by Progressive Education in Islamic boarding schools. Data for this qualitative study was gathered through Focus Group Discussions (FGDs), in-depth interviews and an online communication with 24 teachers from Islamic Boarding Schools in the province of Aceh. The findings indicate that although worries about the issues of the LCI are still arising, the teachers involved in this research believe that the LCI has promising prospects in the near future. The finding also found that although the LCI is considered an efficient method for facilitating optimal learning, it is deemed to be less successful in some courses.